2022
DOI: 10.1007/s11060-022-04180-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of reduced temporal muscle thickness and systemic muscle loss in newly diagnosed glioblastoma patients

Abstract: Purpose Reduced temporal muscle thickness (TMT) has recently been postulated as a prognostic imaging marker and an objective tool to assess patients frailty in glioblastoma. Our aim is to investigate the correlation of TMT and systemic muscle loss to confirm that TMT is an adequate surrogate marker of sarcopenia in newly diagnosed glioblastoma patients. Methods TMT was assessed on preoperative MR-images and skeletal muscle area (SMA) was assessed at the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Many studies have evaluated the relationship between glioblastoma and sarcopenia using TMT. [10,12,[16][17][18][19][20][21] It has been suggested that TMT could guide treatment planning and perioperative processes in patients with glioblastoma. [10] Similarly, TMT has been reported to predict sarcopenia and survival in patients with glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have evaluated the relationship between glioblastoma and sarcopenia using TMT. [10,12,[16][17][18][19][20][21] It has been suggested that TMT could guide treatment planning and perioperative processes in patients with glioblastoma. [10] Similarly, TMT has been reported to predict sarcopenia and survival in patients with glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…TMT is a current parameter for evaluating sarcopenia. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]58,59] A retrospective study by Li et al suggested that TMT is important in evaluating patients' physical condition, stroke recurrence, and survival prognosis after acute stroke. However, they reported that survival time was significantly lower for patients with low than high TMT values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations